Active versus resting neuro‐navigated robotic transcranial magnetic stimulation motor mapping. Issue 12 (24th June 2022) - Kahl, Cynthia K.; Giuffre, Adrianna; Wrightson, James G.; Kirton, Adam; Condliffe, Elizabeth G.; MacMaster, Frank P.; Zewdie, Ephrem
Abstract: Transcranial magnetic stimulation (TMS) motor mapping is a safe, non‐invasive method that can be used to study corticomotor organization. Motor maps are typically acquired at rest, and comparisons to maps obtained during muscle activation have been both limited and contradictory. Understanding the relationship between functional activation of the corticomotor system as recorded by motor mapping is crucial for their use clinically and in research. The present study utilized robotic TMS paired with personalized neuro‐navigation to examine the relationship between resting and active motor map measures and their relationship with motor performance. Twenty healthy right‐handed participants underwent resting and active robotic TMS motor mapping of the first dorsal interosseous to 10% maximum voluntary contraction. Motor map parameters including map area, volume, and measures of map centrality were compared between techniques using paired sample tests of difference and Bland–Altman plots and analysis. Map area, volume, and hotspot magnitude were larger in the active motor maps, while map center of gravity and hotspot locations remained consistent between both maps. No associations were observed between motor maps and motor performance as measured by the Purdue Pegboard Test. Our findings support previous suggestions that maps scale with muscle contraction. Differences in mapping outcomes suggest rest and active motor maps may reflect functionally different corticomotor representations. Advanced analysis methods may better characterize the underlying neurophysiology of both types of motor mapping. Abstract : Understanding the relationship between functional activation of the corticomotor system as recorded by transcranial magnetic stimulation (TMS) motor mapping is crucial for their use clinically and in research. The present study utilized robotic TMS paired with personalized neuro‐navigation to examine the relationship between resting and active motor map measures and their relationship with motor performance. Map area, volume, and hotspot magnitude were larger in the active motor maps, while map centre of gravity and hotspot locations remained consistent between both maps, suggesting that they may reflect functionally different corticomotor representations.